Female police body armour : improving comfort, protection, and testing. - Malbon, Christopher (Cranfield University, 2021)
There is a paucity of published research into female body armour resulting in a lack of evolution in design and testing solutions. A series of surveys and experiments were designed to extend the knowledge relating to female body armour, focusing on comfort, protection, and testing. Comfort was shown to be improved through professional fitting and sizing of new bras, with a sports bra being reported as most comfortable after refitting by 77% of participants. Statistically significant differences in key anthropometric measurements around the breast area were identified between bra types, including bust to bust length, bust circumference, and bust prominence. Exposure of the anterior lateral region of the body was greater compared to the posterior lateral region for female police officers, particularly around the breast area, (exposed anterior lateral breast area – underwired bra: mean 55%, max 72%; sports bra: mean 57%, max 75%). A comparison of three backing materials used for the assessment of back face signature (BFS): Roma Plastilina No1 (RP1); 10% ballistic gelatine; SEBS gel; showed that there were statistically significant differences between the three materials. 10% ballistic gelatine had the greatest variation in measured BFS with both projectiles (9mm; BFS 21.5 – 42.3mm: 0.357”; BFS 31.5 – 67.3mm). RP1 had the smallest variance in measured BFS with both projectiles (9mm; BFS 17.6 – 30.9 mm: 0.357”; BFS 18.9 – 32.5 mm), however, there were statistically significant differences in the spread of results for RP1. The knowledge gained is enabling the development of new guidance for female police officers on improvement in comfort when wearing body armour by the Police Federation. Designers of body armour have information on the effects of bra type on breast shape enabling future designs of body armour to be more tailored to shape, enable a better fit, and reduce the risk of air gaps under the armour. Understanding of the differences in three backing materials will enhance the development of future testing methods for female body armour, which will deliver improvements in the safety of body armour.
© Cranfield University 2021. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner
Keywords: Female body armour (armor); Bras; Roma Plastillina No1; Ballistic gelatine